Комплектування державних архівних установ як предмет історіографічних досліджень - Купченко, В. (Архіви України, 2008)
The article examines historiography of acquisition of state archives, formation of acquisition sources lists, documents appraisal in works and research of Russian and Ukrainian archivists. It highlights the issues of archival fonds optimization, the main cooperation trends with departmental archives and departmental control of work with documents within archival institutions of all levels.